2001
DOI: 10.1021/es001338w
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Biodegradation of Methyl tert-Butyl Ether (MTBE) Using Compound-Specific Carbon Isotope Analysis

Abstract: Methyl tert-butyl ether (MTBE), the most common gasoline oxygenate, is frequently detected in surface water and groundwater. The aim of this study was to evaluate the potential of compound-specific isotope analysis to assess in situ biodegradation of MTBE in groundwater. For that purpose, the effect of relevant physical and biological processes on carbon isotope ratios of MTBE was evaluated in laboratory studies. Carbon isotope fractionation during organic phase/gas-phase partitioning (0.50 ( 0.15‰), aqueous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 38 publications
4
64
0
Order By: Relevance
“…Alkanes n-C15-n-C17 showed the largest fractionation (∼12-25 ( 1.2‰), n-C18 showed an intermediate amount of fractionation (∼8 ( 1.2 ‰), and n-C19-n-C27 showed relatively little fractionation (∼0-6 ( 1.2‰). A possible explanation for this correlation is that during biodegradation the kinetic isotope effects occur mainly with respect to the bond that is broken in the initial transformation step (11). However, our isotopic analyses measure all of the hydrogen atoms in a molecule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkanes n-C15-n-C17 showed the largest fractionation (∼12-25 ( 1.2‰), n-C18 showed an intermediate amount of fractionation (∼8 ( 1.2 ‰), and n-C19-n-C27 showed relatively little fractionation (∼0-6 ( 1.2‰). A possible explanation for this correlation is that during biodegradation the kinetic isotope effects occur mainly with respect to the bond that is broken in the initial transformation step (11). However, our isotopic analyses measure all of the hydrogen atoms in a molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Because the isotopic compositions of pollutants from different sources are generally different, the isotopic profile of a contaminant plume can be used to trace its origin (5,8). Furthermore, during biodegradation the isotopic compositions of residual compounds often become enriched with time (9,11,15), indicating that CSIA can also be used to monitor in-situ bioremediation.…”
Section: Introductionmentioning
confidence: 99%
“…After replacing tetraethyl lead in gasoline, MTBE has become an important groundwater contaminant, and its natural attenuation has been of great interest. 8 Carbon 3 kin values of MTBE measured with microbial cultures clustered around À2& for aerobic degradation, 74,75 but around À9& for anaerobic degradation; 29 hydrogen 3 kin values showed the opposite trend, clustering around À40& in aerobic degradation 74 and around only À10& in anaerobic degradation. 29 A careful analysis in terms of kinetic isotope effects showed that the pronounced hydrogen and small carbon isotope fractionation under aerobic conditions was again consistent with C-H bond cleavage.…”
Section: Deriving Transformation Mechanisms From Isotope Fractionationmentioning
confidence: 88%
“…Degradation of MTBE was absent or very slow in most aquifers (1,6,18). Biodegradation of MTBE was however observed in laboratory experiments under aerobic and anaerobic conditions and resulted occasionally in the transient accumulation of tert-butyl alcohol (TBA) as an intermediate of MTBE degradation (1,(19)(20)(21). Field data on the fate of ethanol at gasoline spill sites are scarce (12), perhaps because ethanol is not a regulated pollutant.…”
Section: Introductionmentioning
confidence: 99%